Mapping the educational landscape for forced migrants in Norway, Ireland and Japan - Solbue, Vibeke; Kenny, Ailbhe; Kitayama, Yuka (Frontiers in Education, 2025)
This review seeks to provide insights into education for forced migrants by mapping the educational landscape in Norway, Ireland, and Japan. The mapping presents the description of the three landscapes, and does not compare statistics of inclusion and education for forced migrants. Taking a human rights perspective, the article discusses forced migration, integration, educational policy, and schools. Various dimensions are then considered through three different country perspectives: educational law, immigrant recognition, and how school systems accommodate (or do not accommodate) forced migrants.